2014
DOI: 10.1136/bcr-2013-202999
|View full text |Cite
|
Sign up to set email alerts
|

Persistent left superior vena cava in association with sinus venosus defect type of atrial septal defect and partial pulmonary venous return on 64-MDCT

Abstract: SUMMARYThe most common venous abnormality of the thorax is persistent left superior vena cava (PLSVC), incidence being less than 0.5%. However, with congenital heart disease, it is about 6.1%. When the coronary sinus is dilated always search for PLSVC. The coronary sinus may communicate with the left atrium. This is known as an unroofed coronary sinus (UCS) and preoperatively documenting it is important. Of all the congenital cardiac anomalies, the sinus venosus defect (SVD) type of atrial septal defect (ASD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…The SVASD type affects about 4% to 11% of all ASDs associated with the persistent left SVC. 29 In the present study, the persistent left SVC was more frequent in patients with the SVASD. Evaluating the abnormalities of the interatrial septum and anomalies concomitant with ASD requires multimodality assessments including TTE, TEE, intracranial ultrasound, and ultimately 3D imaging.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The SVASD type affects about 4% to 11% of all ASDs associated with the persistent left SVC. 29 In the present study, the persistent left SVC was more frequent in patients with the SVASD. Evaluating the abnormalities of the interatrial septum and anomalies concomitant with ASD requires multimodality assessments including TTE, TEE, intracranial ultrasound, and ultimately 3D imaging.…”
Section: Discussionsupporting
confidence: 53%
“…The persistent left SVC is the most common thoracic venous anomaly 29 , 30 with an incidence rate of 0.3% to 0.5% in the general population and 3% to 10% in patients with congenital heart diseases. 31 , 32 The condition is caused by a failure in the regression of the left anterior cardinal vein during cardiac development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of LSVC can also be identified by catheterization via the right upper limb vein, if the catheter tip passed through the RA appears in the left superior mediastinum. Studies have reported that diagnosis of UCSS was more likely by transesophageal echocardiography (TEE), real‐time three‐dimensional echocardiography, or magnetic resonance imaging (MRI) 6–8 . In recent years, several cases of TTE diagnosis errors have been reported, which were subsequently correctly diagnosed as UCSS by TEE, multidetector computed tomography (MDCT), or MRI 9–11 …”
Section: Discussionmentioning
confidence: 99%
“…Cardiac catheterization examination via the left upper limb venous catheterization was easy to find LSVC; if catheterization via the right upper limb vein and catheter tip through the right atrium and then appeared in the left superior mediastinum, it also suggested the presence of LSVC. It was reported that it was more likely to diagnose UCSS using transesophageal echocardiography (TEE), real-time threedimensional echocardiography, or magnetic resonance imaging (MRI) [6][7][8]. In recent years, several cases of TTE diagnosis errors have been reported, which have been diagnosed as UCSS by TEE, MDCT or MRI [9][10][11].…”
Section: Preoperative Diagnosismentioning
confidence: 99%